Case Report: 3D Printing Guided Cardiac Autotransplantation for Treatment of a Giant Complex Primary Left Atrial Tumor - Zhou, Yang-zhao; Tang, Tao; Luo, Cheng; Zhou, Xin-min; Fu, Xian-ming (Frontiers in Cardiovascular Medicine, 2021)
Primary cardiac tumors are rare and complete surgical resection is the optimal treatment. However, it is a great challenge to resect some malignant or complex benign left-sided cardiac tumors situated on the posterior aspect of the heart using conventional surgical resection techniques. Previous studies reported that cardiac autotransplantation is a feasible and safe technique for resection of such cardiac tumors. We report a successful case of cardiac autotransplantation with 3-dimensional (3D) printing technique for complete resection of a giant complex primary left atrial tumor.